Theatre - Weibull, Lennart (University of Gothenburg, 1992)
The purpose of this survey is to see how theatre habits interplay with different leisure-time activities and other media habits. To investigate this the audience of three performances of the play ´Nicholas Nickleby´ were asked to fill in a questionnaire handled over at the entrance. The questions dealt with paper reading; preferences of TV-programs; book reading habits; activities during the last 12 months; theatre visits during the last 12 months; theatres visited; theatrical form preferred. There were also a number of questions concerning the respondent´s background.

The purpose of this survey is to see how theatre habits interplay with different leisure-time activities and other media habits. To investigate this the audience of three performances of the play ´Nicholas Nickleby´ were asked to fill in a questionnaire handled over at the entrance. The questions dealt with paper reading; preferences of TV-programs; book reading habits; activities during the last 12 months; theatre visits during the last 12 months; theatres visited; theatrical form preferred. There were also a number of questions concerning the respondent´s background.
Teater
Keywords: book use; bokanvändning; television programmes; tv-program; theatre attendance; teaterbesök; Cultural activities and participation; Kulturaktiviteter och deltagande; Social Sciences; Samhällsvetenskap